Complementary and Alternative Therapies for Weight Loss: A Narrative Review - Pei Lin Lua PhD; Nurul Afiedia Roslim MSc, PhD; Aryati Ahmad PhD; Mardiana Mansor MSc; Myat Moe Thwe Aung MD; Farrahdilla Hamzah MSc (SAGE Publishing, 2021)
Despite various strategies, overweight and obesity problems are still increasingly prevalent worldwide with serious health outcomes. Consequently, the continuous demand for more effective, safe and acceptable therapies for reducing body weight is also escalating-including complementary and alternative therapies (CATs). The aim of this review is to provide a summary of the most commonly- and recently-used CATs, with evaluation of their safety and efficacy for weight loss. Electronic scientific databases such as Scopus, PubMed and EBSCO Host were explored for articles that reported CATs for overweight and obesity treatment from 2015 to December 2019. Only systematic reviews, meta-analysis and randomized controlled trials (RCTs) published in English were included. Studies whereby CATs were not utilized for reducing body weight were excluded. Eight systematic reviews and meta-analyses and 11 additional RCTs with 765 participants (50.2% overweight and 49.8% obese) related to hypnotherapy, acupuncture and dietary supplements met the inclusion criteria. Their results suggested that spirulina, chitosan, probiotic, EPA + DHA, vitamin D, fiber, and herbal extract supplementation may all provide small reductions in body weight (ranging from 1-10 kg). Interestingly, hypnotherapy and acupuncture reported significantly greater reduction in body weight compared with placebo (p < 0.001 and p < 0.0001, respectively). Nonetheless, the evidence is still relatively limited and not encouraging to provide a definitive conclusion due to the methodological shortcomings and the presence of adverse events in chitosan and fiber supplementation. Hence, studies of this nature need to be further replicated and improved to corroborate the efficacy and safety of the CATs to combat weight issues.